Mothers and Parental Leave in Belgium: Social Inequalities in Eligibility and Uptake - Marynissen, Leen (Social Inclusion, 2021)
In recent decades, many Western European countries introduced parental leave policies to support the work-family combination in families with young children. However, these parental leave schemes often exhibit employment‐based eligibility criteria, so the question arises to which extent social inequalities emerge in the access to parental leave, and as a result thereof also in the uptake of parental leave. Although research on parental leave increasingly addresses the issue of inclusiveness, only a limited number of studies has yet examined individual‐level differentials in parents’, and especially mothers’, eligibility. Using detailed register data, we develop an individual‐level indicator of eligibility in Belgium and deploy it to document differentiation in mothers’ eligibility by age at first birth, partnership status, migration background and education. In addition, we examine to what extent differential eligibility can explain inequalities in parental leave uptake. Our results show that a considerable share of mothers—specifically very young, single, low educated mothers and mothers with a migration background—do not meet the eligibility criteria and thus are structurally excluded from parental leave in Belgium. Furthermore, differential eligibility can account for a large part of the age and educational gradients in parental leave use, as well as differences by migration background. Eligibility cannot (fully) account for lower parental leave use by single mothers and mothers with a Moroccan or Turkish migration background. Our findings suggest that a reconsideration of eligibility criteria may be instrumental in increasing the inclusiveness of parental leave policies.